Application of Al2O3 ceramic for a circularly polarized filtering antenna - Ke Xia; Hai-Feng Zhang (Alexandria Engineering Journal, 2024)
The application of ceramic for a circularly polarized (CP) filtering antenna is studied in this paper. The dielectric resonator (DR) of sintered aluminum oxide (Al2O3) ceramic has a dielectric constant of 9.5 and low dielectric loss of 0.003, and excellent mechanical properties. The dielectric resonator antenna (DRA) consists of two parts, the upper part is a DR, and the lower part uses a feeding network containing two hairpin bandpass filters. The measured |S11| of the DRA is 48.0 % and the axial ratio (AR) bandwidth is 33.5 %. Meanwhile, the peak gain of the DRA is 6.13 dBi, and the suppression level across the stopband exceeds 15.2 dB. The DRA uses the hairpin bandpass filters to improve the filtering characteristics of the antenna and uses the corner-cutting processing of the DR to improve the AR, which can be implemented to reduce the cost of fifth-generation (5 G) communication.